Erosive wear behaviour of hardfacing austenitic manganese deposit - Yildizli, Kemal; Ero?lu, Mehmet; Karamiş, M. Baki (My University, 2005)
The solid particle erosion wear behaviors of hardfacing austenitic-manganese deposited layers on the low carbon steel surface were experimentally studied at intermediate and normal impact angles. The specimens were surfaced with single, double and triple pass bead on-plate welds using SMAW with austenitic-manganese electrode, respectively. Erosion tests were conducted at impact angles of 30, 60 and 90° using angular hard erodent. The results showed that the erosion rate varied as a function of the impact angles, and that the highest wear occurred at 90°. All layers had relatively higher erosion resistant at oblique impact than those of normal impact. The first layer exhibited the highest resistance to erosion, because of intensive martensitic microstructure. The repeated impacts caused plastic flow in relatively softer surface of the second and third layer and material removal occurs by microcutting and microploughing. During the erosive wear progress for samples with multilayer pass welding, in just below eroded surface, remarkable plastic deformation were simultaneously observed with work hardening and strain-induced martensitic transformation from austenite. This also increased the hardness of the layer.
Keywords: Hardfacing austenitic manganese electrode; Solid particle erosion